Crystallization kinetics, morphology, and mechanical properties of novel poly(ethylene succinate-co-octamethylene succinate). (December 2015) - Li, Xiaojing; Qiu, Zhaobin
Abstract: The crystallization kinetics, morphology and mechanical properties of a novel poly(ethylene succinate- co -octamethylene succinate) (PEOS) copolyester with 82 mol% ethylene succinate (ES) units and 18 mol% octamethylene succinate (OS) units, and its homopolymer poly(ethylene succinate) (PES) were extensively investigated. The glass transition temperature, cold crystallization peak temperature and melting point of PEOS are around −24, 47.5, and 80.5 °C, respectively. The Avrami equation was used to analyze the isothermal melt crystallization kinetics of PEOS and PES. They display the same crystallization mechanism, and PEOS crystallizes slower than PES at the same degree of supercooling. The spherulitic growth rates of PEOS and PES exhibit a bell shape within the investigated crystallization temperature range, with the crystallization regime transition temperature of PEOS being lower than that of PES. In addition, PEOS has high thermal stability and good mechanical properties.